Numerical investigation into the evaporation dynamics of drop-on-drop collisions over heated wetting surfaces. (August 2018) - Guggilla, Ganesh; Pattamatta, Arvind; Narayanaswamy, Ramesh
Highlights: Drop-on-drop impingement over superheated surfaces is numerically investigated. Comparison of single drop with drop-on-drop impingement is presented. The effect of influencing parameters on the evaporation dynamics is assessed. An analytical model for maximum spread factor for drop-on-drop impact is developed. Abstract: The present study aims at the numerical investigation of drop-on-drop impingement over heated surfaces. Drop-on-drop impact has been found to be one of the basic processes in spray cooling applications. A two-phase solver implemented in open source CFD toolbox OpenFOAM, is used with VOF interface tracking technique which considers contact line evaporation and dynamic contact line motion. This numerical model is validated using the experimental data available in literature for single drop-hot wall interactions. The hydrodynamic behaviour (in terms of spread factor) and evaporation dynamics (in terms of input and evaporation heat transfers) of drop-on-drop impingement is compared to a single drop impact over a heated surface under similar conditions. It was found that the spread factor is higher for drop-on-drop impingement than the single droplet impact. However, high input and evaporation heat transfers were observed for the case of single droplet due to the high spread surface area-to-volume ratio. In addition, a parametric study is carried out to study the effect of some of the influencing parameters on the drop-on-drop impingement, choosing Weber number (We), Bond number (Bo), Jakob number (Ja) and Radius ratio (R ∗ ) as parameters. Results showed that all these parameters substantially affect the spread and evaporation dynamics of the drop-on-drop collision over a heated surface. Also based on the conservation of energy principle, an analytical model is developed to find the maximum spread factor. In order to quantify the simulation heat transfer effects, a correlation for input heat transfer available in the literature is used to review the numerical findings. Both theoretical and simulation results are in good agreement with a maximum deviation of 10% in spread factor and 20% in input heat transfer prediction.